The N-Methyl-D-Aspartate Receptor Blocker REL-1017 (Esmethadone) Reduces Calcium Influx Induced by Glutamate, Quinolinic Acid, and Gentamicin - Ezio Bettini; Sara De Martin; Andrea Mattarei; Marco Pappagallo; Stephen M. Stahl; Francesco Bifari; Charles E. Inturrisi; Franco Folli; Sergio Traversa; Paolo L. Manfredi (MDPI AG, 2022)
REL-1017 (esmethadone) is a novel N-methyl-D-aspartate receptor (NMDAR) antagonist and promising rapid antidepressant candidate. Using fluorometric imaging plate reader (FLIPR) assays, we studied the effects of quinolinic acid (QA) and gentamicin, with or without L-glutamate and REL-1017, on intracellular calcium ([Ca2+]in) in recombinant cell lines expressing human GluN1-GluN2A, GluN1-GluN2B, GluN1-GluN2C, and GluN1-GluN2D NMDAR subtypes. There were no effects of QA on [Ca2+]in in cells expressing GluN1-GluN2C subtypes. QA acted as a low-potency, subtype-selective, NMDAR partial agonist in GluN1-GluN2A, GluN1-GluN2B, and GluN1-GluN2D subtypes. REL-1017 reduced [Ca2+]in induced by QA. In cells expressing the GluN1-GluN2D subtype, QA acted as an agonist in the presence of 0.04 μM L-glutamate and as an antagonist in the presence of 0.2 μM L-glutamate. REL-1017 reduced [Ca2+]in induced by L-glutamate alone and with QA in all cell lines. In the absence of L-glutamate, gentamicin had no effect. Gentamicin was a positive modulator for GluN1-GluN2B subtypes at 10 μM L-glutamate, for GluN1-GluN2A at 0.2 μM L-glutamate, and for GluN1-GluN2A, GluN1-GluN2B, and GluN1-GluN2D at 0.04 μM L-glutamate. No significant changes were observed with GluN1-GluN2C NMDARs. REL-1017 reduced [Ca2+]in induced by the addition of L-glutamate in all NMDAR cell lines in the presence or absence of gentamicin. In conclusion, REL-1017 reduced [Ca2+]in induced by L-glutamate alone and when increased by QA and gentamicin. REL-1017 may protect cells from excessive calcium entry via NMDARs hyperactivated by endogenous and exogenous molecules.